Factors associated to risk of malnutrition amongst elderly women in low-income communities (Colombia Medica, 2012)
Objective: The present study aimed to identify the prevalence and the factors associated with the risk of malnutrition in elderly women. Methods: The study deals with a cross-sectional design, with a sample of 222 women in the age group from 60 to 96 years of age. An interview was carried out containing socio-demographic variables, clinical conditions, and behavioral aspects. The statistical analysis was accomplished via calculation of the respective prevalence ratios (PR) in the Poisson regression, p